Population Studies and Development from Theory to Fieldwork (Demographic Transformation and Socio-Economic Development,, 2018)
This book addresses major population and development issues: fertility and reproductive health, migrations, gender, education, poverty and inequalities. To that aim it revisits and considerably enlarges Kingsley Davis' 1963 theory of change and response, using interdisciplinary methodologies. On the basis of four decades of field research (1985-2015), it questions the rationality of the actors, how culture shapes socio-demographic behaviours, in a context of modernity and globalisation. More specifically, it casts new light on the interactions of individuals, families, networks and local communities with the State and its population policy.